Nursing team knowledge about care for patients under hemodialysis: Integrative review (Research, Society and Development, 2024)
This research aims to investigate the knowledge of nursing professionals about the care of hemodialysis patients, analyzing the results of previous studies published on this specific topic. Methods: Searches for articles were carried out in February and March 2024, using the Virtual Health Library (VHL), focusing on the Latin American and Caribbean Literature in Health Sciences (LILACS) and BDENF - Nursing. The search terms included "hemodialysis", "nephrology nursing" and "nursing care", resulting in 148 articles. After inclusion and exclusion criteria, 6 articles were selected for this research, due to their relevance to the proposed objectives. Results: The research revealed a significant lack of knowledge among nursing professionals about hemodialysis care, highlighting the urgent need for investment in training and continuing education in this area. This lack of knowledge can directly impact the quality of care provided to hemodialysis patients, highlighting the importance of initiatives to fill this need and ensure evidence-based clinical practice. Conclusions: Investing in the knowledge and training of hemodialysis nurses not only improves the quality of care provided, but also contributes to better clinical outcomes and patient satisfaction. This integrative review serves as a call to action to promote a more robust and informed approach to hemodialysis care management.